Sosialisasi Produk Murabahah (Pembiayaan Usaha Mikro) Bank Syariah Mandiri Cabang Jember kepada Pengurus Dasa Wisma Perumahan Alam Hijau RT. 04 Sempusari Jember - Muhammad Syafi’i (Mujtama': Jurnal Pengabdian Masyarakat, 2021)
Islam belongs to religion that is rahmatan lil alamin, in that it teaches all dimensions of human life. One of them is related to the economy. In this context, Islam is very detailed in teaching the process of doing transactions, pawning, lending, etc. Lending can be done between individuals by involving intermediaries such as banks or other financial institutions. The Islamic teaching is this context concerns how such practice (lending) may be done. This, for instance, concerns regulating interests which, in Islamic teaching, is considered usury (riba). This usury practice still applies in the country like Indonesia, even though the majority of the population in this country is Muslim. Put another way, many Indonesians are still bound to conventional banking systems which necessitate usury. Therefore, it is necessary to resurrect the teaching of Islam to prevent people from relying on these “prohibited” services. This can be done by introducing alternative banking and non-banking systems that implement Islamic teaching to the general public by collaborating with other parties such as sharia banks as well as academic institutions. In doing so, the Muslim community will be more familiar with sharia banking and, thus, may prevent them from relying on conventional banking practices to using the principles of murabahah provided by sharia banking